2009
DOI: 10.1103/physrevlett.102.016403
|View full text |Cite
|
Sign up to set email alerts
|

Strong Parity Mixing in the Fulde-Ferrell-Larkin-Ovchinnikov Superconductivity in Systems with Coexisting Spin and Charge Fluctuations

Abstract: We study the Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state of spin fluctuation mediated pairing, and focus on the effect of coexisting charge fluctuations. We find that (i) consecutive transitions from singlet pairing to FFLO and further to S_{z}=1 triplet pairing can generally take place upon increasing the magnetic field when strong charge fluctuations coexist with spin fluctuations, and (ii) the enhancement of the charge fluctuations lead to a significant increase of the parity mixing in the FFLO state, whe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 38 publications
3
29
0
Order By: Relevance
“…Both possibilities have been asserted theoretically. 23,[69][70][71][72][73][74][75][76][77][78][79][80] Many authors [69][70][71][72][73][74][75][76][77][78][79][80] have not taken account of t 3 , t 4 , and V in the theoretical study while a few authors have studied with V and t 3 in Refs. 75 and 80, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Both possibilities have been asserted theoretically. 23,[69][70][71][72][73][74][75][76][77][78][79][80] Many authors [69][70][71][72][73][74][75][76][77][78][79][80] have not taken account of t 3 , t 4 , and V in the theoretical study while a few authors have studied with V and t 3 in Refs. 75 and 80, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[14,15,16,17,19,26,25] where the site representation [26] for singlet and triplet pairing interactions are given respectively aŝ…”
Section: Pairing Interactions and Gap Equationmentioning
confidence: 99%
“…The single band models for (TMTSF) 2 PF 6 has been investigated by perturbation theories. [14,15,16,17,18,19] The magnetic field favors the triplet or FFLO superconductivity, [16,17,18] while the on-site repulsion induces the singlet superconductivity in the absence of magnetic field. [19] The interplay between the spin and charge fluctuations in the triplet superconductivity has been investigated by the renormalization group theories.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently, it has been suggested that it occurs in strongly Pauli-limited clean type-II superconductors, such as the heavy-fermion superconductor CeCoIn 5 4) and the quasi-low-dimensional organic superconductors κ-(BEDT-TTF) 2 Cu(NCS) 2 , [10][11][12][13] λ-(BETS) 2 FeCl 4 , [16][17][18] λ-(BETS) 2 GaCl 4 , 19) and (TMTSF) 2 ClO 4 . [20][21][22][23][24][25][26][27] Quasi-low-dimensionality is a common feature of the above-mentioned compounds. It stabilizes the FFLO state for two reasons.…”
Section: Introductionmentioning
confidence: 99%
“…In anisotropic superconductors, the structure of the gap function significantly affects the Fermi-surface effect. 8,9) In the present study, the Fermi-surface effect in quasione-dimensional (Q1D) s-wave and d-wave superconductors is investigated, motivated by studies of the Q1D organic superconductors (TMTSF) 2 X, which may exhibit an FFLO state, [5][6][7][20][21][22][23][24][25][26][27] where TMTSF stands for tetramethyltetraselenafulvalene, and X = ClO 4 , PF 6 , etc. In (TMTSF) 2 PF 6 , Lee et al found an upturn of H c2 (T ) at low temperatures, that exceeds the Pauli paramagnetic limit H P .…”
Section: Introductionmentioning
confidence: 99%